(untitled) (Journal of the College of Basic Education, 2022)
Water is the basis and pillar of life. Civilizations have flourished wherever water is abundant, and it is a resource that has become more important than many other natural resources. Its deficiency or deterioration in its quality has economic, social and environmental effects. Two things are very important for societies that seek development and development